DEVELOPMENT OF A GUIDEBOOK FOR BASED CHEMISTRY PRACTICES GREEN CHEMISTRY IN REACTION RATE MATERIALS - Harahap, Siti Rahma Dani; Sutiani, Ani (Jurnal Ilmu Pendidikan Indonesia, 2023)
Practical activities are an important part of chemistry education. The chemistry practicum faced a variety of issues, including a lack of school facilities for performing the practicum and improperly managed chemical waste. As a reason, the research aims to develop and validate the feasibility of a green chemistry-based laboratory manual, as well as to assess how students and teachers respond to the final product. Research and Development (R&D) using the ADDIE model was employed as the research methodology. The reaction rate is the subject of this study. The laboratory manual developed is very feasible to implement in chemistry learning, according to the results of the analyzed data. Media expert lecturers provide an average score of 90 percent (very feasible) and material expert lecturers provide a score of 93,9 percent (very feasible). Students and teachers responded enthusiastically to the developed laboratory manual, with an average student reaction of 85 percent (very good) and a teacher response of 93,4 percent (very good).